Regulation of the Mitochondrion-Fatty Acid Axis for the Metabolic Reprogramming of Chlamydia trachomatis during Treatment with β-Lactam Antimicrobials - Shima, Kensuke; Kaufhold, Inga; Eder, Thomas; Käding, Nadja; Schmidt, Nis; Ogunsulire, Iretiolu M.; Deenen, René; Köhrer, Karl; Friedrich, Dirk; Isay, Sophie E.; Grebien, Florian; Klinger, Matthias; et al. (mBio, 2021)
The mitochondrion generates most of the ATP in eukaryotic cells, and its activity is used for controlling the intracellular growth of Chlamydia trachomatis . Furthermore, mitochondrial activity is tightly connected to host fatty acid synthesis that is indispensable for chlamydial membrane biogenesis. Infection with the obligate intracellular bacterium Chlamydia trachomatis is the most common bacterial sexually transmitted disease worldwide. Since no vaccine is available to date, antimicrobial therapy is the only alternative in C. trachomatis infection. However, changes in chlamydial replicative activity and the occurrence of chlamydial persistence caused by diverse stimuli have been proven to impair treatment effectiveness. Here, we report the mechanism for C. trachomatis regulating host signaling processes and mitochondrial function, which can be used for chlamydial metabolic reprogramming during treatment with β-lactam antimicrobials. Activation of signal transducer and activator of transcription 3 (STAT3) is a well-known host response in various bacterial and viral infections. In C. trachomatis infection, inactivation of STAT3 by host protein tyrosine phosphatases increased mitochondrial respiration in both the absence and presence of β-lactam antimicrobials. However, during treatment with β-lactam antimicrobials, C. trachomatis increased the production of citrate as well as the activity of host ATP-citrate lyase involved in fatty acid synthesis. Concomitantly, chlamydial metabolism switched from the tricarboxylic acid cycle to fatty acid synthesis. This metabolic switch was a unique response in treatment with β-lactam antimicrobials and was not observed in gamma interferon (IFN-γ)-induced persistent infection. Inhibition of fatty acid synthesis was able to attenuate β-lactam-induced chlamydial persistence. Our findings highlight the importance of the mitochondrion-fatty acid interplay for the metabolic reprogramming of C. trachomatis during treatment with β-lactam antimicrobials. IMPORTANCE The mitochondrion generates most of the ATP in eukaryotic cells, and its activity is used for controlling the intracellular growth of Chlamydia trachomatis . Furthermore, mitochondrial activity is tightly connected to host fatty acid synthesis that is indispensable for chlamydial membrane biogenesis. Phospholipids, which are composed of fatty acids, are the central components of the bacterial membrane and play a crucial role in the protection against antimicrobials. Chlamydial persistence that is induced by various stimuli is clinically relevant. While one of the well-recognized inducers, β-lactam antimicrobials, has been used to characterize chlamydial persistence, little is known about the role of mitochondria in persistent infection. Here, we demonstrate how C. trachomatis undergoes metabolic reprogramming to switch from the tricarboxylic acid cycle to fatty acid synthesis with promoted host mitochondrial activity in response to treatment with β-lactam antimicrobials.